The Role of the Prosecutor in Executing the Payment of Replacement Money - Artha, I Gede; Adiyaryani, Ni Nengah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 3 (2020)DO - 10.24843/JMHU.2020.v09.i03.p05, 2020)
This research is about the role of the Prosecutor as an executor in executing the assets of the convicts of corruption, to recover the State financial losses from corruption. Besides that, this research aims to know about the returning of State financial losses through the payment of replacement money. Corruption is an extraordinary crime, veiled and endanger national stability and security and inhibiting Indonesian economic development. This research is a normative legal research with primary, secondary and tertiary legal material supported by data. This research is using statutory, case , and compar ative approach es . The legal basis used in this research are Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, Law No. 16 of 2004 and Law No. 8 of 1981 (Indonesian Criminal Procedural Code). The corruption has become systematic and the scope enters into all aspect of life, start with the lower level with State Officers and law enforcers becomes the dominant actors. In imposing the sanction, The Judges are not only charge imprisonment but also charge additional fines and/or penalties to returning the State financial losses and ask the convicts of corruption to pay the replacement money to the State. The problem arises in this research related to the execution of the verdict about returning State financial losses which are the assets of the convicted person is already in the third party hands or have been depleted, dual population administration, the length of the judicial process, the convicted person prefers to take the subsidiary criminal charge and the hollow of norm regarding technical execution for the Prosecutors so that the execution cannot be carried out.